2015
DOI: 10.1016/j.envsci.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Who should do what in environmental management? Twelve principles for allocating responsibilities

Abstract: In environmental management there is often discussion on the allocation of responsibilities. Such discussions can continue for a long time and can form an obstacle for effective action. In this article twelve normative principles for the allocation of responsibilities are identified, coming from three different sources: the arguments used in discussions on responsibilities, Dutch and European law, and the environmental management literature. The principles are 1) capacity, 2) lowest social costs, 3) causation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…If vague responsibilities hamper climate adaptation, conversely a more explicit allocation of responsibilities could drive climate adaptation. It is suggested that the formal allocation of responsibilities facilitates and structures the collaboration between actors , and gives legitimacy to the actors (Mostert, 2015). In addition to providing clarity of responsibilities, it also matters who takes on responsibilities (Mostert, 2015): it matters how the different public and private actors divide responsibilities for climate adaptation in their cities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If vague responsibilities hamper climate adaptation, conversely a more explicit allocation of responsibilities could drive climate adaptation. It is suggested that the formal allocation of responsibilities facilitates and structures the collaboration between actors , and gives legitimacy to the actors (Mostert, 2015). In addition to providing clarity of responsibilities, it also matters who takes on responsibilities (Mostert, 2015): it matters how the different public and private actors divide responsibilities for climate adaptation in their cities.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the formal allocation of responsibilities facilitates and structures the collaboration between actors , and gives legitimacy to the actors (Mostert, 2015). In addition to providing clarity of responsibilities, it also matters who takes on responsibilities (Mostert, 2015): it matters how the different public and private actors divide responsibilities for climate adaptation in their cities. Public actors, such as for instance urban planners, water managers and health officers, may decide to bear responsibility for adaptation action so that present and future generations are sufficiently protected against climate impacts (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Completely national management is problematic too because it would result in a separation between decision-making, financing and benefits; increases dependence on national politics; and reduce the possibilities to take local conditions and preferences into account and to experiment (cf. Mostert 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Issues such as local flooding and pollution hotspots have a smaller geographical scope, whereas issues such as inter-basin water transfers and continental water recycling have a much larger scope (e.g. Hoekstra 2010, Van der Ent et al 2010, Mostert 2015, Pande and Sivapalan 2016. Outside of the water sector the river basin scale often is not important at all.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation